Employment status monitoring in an Argentinian population of patients with multiple sclerosis: Particularities of a developing country. - Vanotti, S.; Eizaguirre, M.B.; Ciufia, N.P.; Yastremiz, C.M.; Roman, M.S.; Canyazo, C. Martinez; Alonso, R.; Garcea, O.; Benedict, R.H.B.; Caceres, F. (Work, 2021)
BACKGROUND: Multiple sclerosis (MS) is a neurological chronic disease that causes a number of physical, cognitive and emotional symptoms. The identification of these factors will allow mitigating unemployment and improve quality of life of patients. The Buffalo Vocational Monitoring Survey (BVMS) is a tool to characterize Work-Challenged patients. OBJECTIVE: To describe and analyze BVMS data in people with multiple sclerosis (PwMS) from Argentina. To study the association with physical, cognitive and psychiatric morbidity in employed patients, comparing the performance of MS Work-Challenged and MS Work-Stable patients, with and without accommodations. METHODS: 119 MS patients were administered the Argentina adaptation of the BVMS, and completed measures of physical disability, fatigue, depression, cognitive processing speed, memory and verbal fluency. RESULTS: 65.54% of the patients were employed and 19.32% were unemployed, the remaining having roles of housewife, students and disability retirees. Within the employed subgroup, 60.26% were working as employees and 39.74% were self-employed. Cognitive and clinical variables differentiate patients with and without negative events and accommodations (p > 0.05). CONCLUSIONS: This Spanish version BVMS is considered a new tool to monitor employment difficulties in Spanish-speaking MS patients. MS Work-Challenged had a higher depression, fatigue and worse performance in cognitive variables.